On the automorphism group of certain simple $C^*$-algebras - Mygind, Jesper (MATHEMATICA SCANDINAVICA, 2004)
We show that the information contained in $KL(A,B)$ is determined by other invariants when $A$ and $B$ are certain simple unital projectionless $C^*$-algebras. This allows us to compute the group of automorphisms modulo the group of approximately inner automorphisms in terms of the Elliott invariant.